Pola Spasial berbasis Perapian di Kawasan Pegunungan Dusun Karangtengah, Banjarnegara - Yohanes Basuki Dwisusanto; Hermawan (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2020)
Spatial patterns are formed based on local wisdom and Karangtengah Hamlet settlement which is located in the cold climate of the mountainous area in Banjarnegara Regency, Central Java has been discovered to have a uniqueness in using the fireplace as the center of its activities. Therefore, this research was conducted to uncover the basic concept of fireplace-based house spatial pattern in this settlement using a qualitative method which involves combining interview, observation, and documentation. The process also involved using 33 houses as the case study with the criterion for selection being the active use of the fireplace. The results showed the placement of fireplace in these houses was influenced by the kinship system and the purpose was to have spatial patterns designed to reduce migration from these settlements to cities.